Economic burden of enhanced practices of duodenoscopes reprocessing and surveillance: balancing risk and cost containment - Bomman, Shivanand; Kozarek, Richard A.; Thaker, Adarsh M.; Kodama, Camilla; Muthusamy, V. Raman; Ross, Andrew S.; Krishnamoorthi, Rajesh (Endoscopy International Open, 2021)
Background and study aims Recent outbreaks attributed to contaminated duodenoscopes have led to the development of enhanced surveillance and reprocessing techniques (enhanced-SRT) aimed at minimizing cross-contamination. Common enhanced-SRT include double high-level disinfection (HLD), ethylene oxide (EtO) gas sterilization, and culture-based monitoring of reprocessed scopes. Adoption of these methods adds to the operational costs and we aimed to assess its economic impact to an institution.Methods We compared the estimated costs of three enhanced-SRT versus single-HLD using data from two institutions. We examined the cost of capital measured as scope inventory and frequency of scope use per unit time, the constituent reprocessing costs required on a per-cycle basis, and labor & staffing needs. The economic impact attributable to enhanced-SRT was defined as the difference between the total cost of enhanced-SRT and single HLD.Results Compared to single HLD, adoption of double HLD increased the costs approximately by 47 % ($80 vs $118). Similarly, culture and quarantine and EtO sterilization increased costs by 160 % and 270 %, respectively ($80 vs $208 and $296). Enhanced-SRT introduced significant scope downtime due to prolonged techniques, necessitating a 3.4-fold increase in the number of scopes needed to maintain procedural volume. The additional annual budget required to implement enhanced-SRT approached $406,000 per year in high-volume centers.Conclusions While enhanced-SRT may reduce patient risk of exposure to contaminated duodenoscopes, it significantly increases the cost of performing ERCP. Future innovation should focus on approaches that can ensure patient safety while maintaining the ability to perform ERCP in a cost-effective manner.